Development of Islamic boarding school curriculum through equalization policies - Firdaus, Wildani; Mardiana, Dina (UIN Salatiga, 2024)
This study aims to find out the existence of the mu'adalah curriculum in the global era as well as to know the challenges of implementing the mu'adalah curriculum after the issuance of the Minister of Religious Affairs Regulation (PMA) number 18 of 2014. Global changes, technological and scientific developments, and the development of art and culture are the basis for changes in the education system, namely the curriculum. This is done so that educational institutions, especially Islamic boarding schools, can adapt and be able to compete with existing developments. This research method uses a qualitative approach with the type of library research. The results of this study state that the existence of Islamic boarding schools has not regressed at all to date. This is because Islamic boarding schools received recognition from the government with the mu'adalah policy which was strengthened by the birth of the Minister of Religious Affairs Regulation (PMA) Number 18 of 2014 which was able to make Islamic boarding schools able to compete with any educational institution. But of course, challenges related to it cannot be avoided. One of them, some people question the quality of mu'adalah Islamic boarding school graduates who do not take the national exam.